Canadian Studies and the Arctic - Adams, W.P. (ARCTIC, 1976)
… In 1972, the Association of Universities and Colleges of Canada (AUCC) reacted in a moderate fashion to the concern about the lack of Canadian content in the educational system by establishing a Commission on Canadian Studies "to study, report and make recommendations upon the state of teaching and research in various fields of study relating to Canada and Canadian universities." The present commentary is based upon the first two volumes of the four-volume report of the Commission. The extraordinary scope of their painstaking enquiry, which will have synthesized a very large number of briefs and letters and a mass of information gained at public and private meetings, is indicated by the following list of principal topics covered in these first two volumes: Canadian content in the university curriculum - contains quite detailed statements on more than twenty subjects including those of particular relevance to the Arctic. Science, technology and Canadian Studies - includes a great deal of material of northern relevance. The Canadian component in education for the professions - refers to products of Canadian technology such as snowmobiles and snow removal equipment. Canadian Studies abroad - mention made of the Arctic. Canadian Studies in community colleges - includes specific recommendations for the development of colleges in the North. Archives and Canadian Studies - a topic of interest to those institutions maintaining northern records. Audio-visual resources and other media support for Canadian Studies. The private donor and Canadian Studies. The whole Report is introduced by a discussion of a rationale for Canadian Studies, and is of importance in that it indicates the way in which the Commission's findings are presented and the nature and tone of the hundreds of recommendations made by them. … The relative failure of Canadian university programmes in and about the North (and this failure appears to have been greater in teaching than in research, although the latter is inextricably bound up with the former ...